PENILAIAN POSTUR PEKERJA DENGAN MENGGUNAKAN METODE RAPID OFFICE STRAIN ASSESSMENT (ROSA) DI PT UNILEVER BALIKPAPAN - Muhamad Ramdan; L.M. Zainul; Muhammad Kurniawan (IDENTIFIKASI, 2022)
PT Unilever is a business that uses computers in its daily operations. At PT Unilever Balikpapan, computers are used in every department. 90% of employees use computers as work aids in public services, shipping, goods, engineering, and finance departments. Rapid Office Strain Assessment is an ergonomics assessment method for office and computer-related or administrative work. Rapid Office Strain Assessment is one of the office ergonomics techniques used to analyze the risks of computer use and decide what level of adjustment measures to take in response to reports of pain. ROSA observations are used to evaluate ergonomic risks in office workers, which can lead to musculoskeletal disorders. By using the Rapid Office Strain Evaluation approach, the assessment is carried out by looking at the employee's work posture. a picture of a worker to be measured. ROSA is a useful tool and one of the easiest methods to assess several risk factors associated with complaints in the form of work-related injuries to muscles, tendons, and body structures. Risk factors from computer use are divided into chairs, monitors, telephones, keyboards, and mice. The method for assessing ROSA is by assessing an increase of 1–3 for each work factor risk. The final result of the ROSA assessment will be a value ranging from 1 to 10. If the final value obtained is greater than 5, then the work is considered risky. In addition, the duration of work time is also considered. The Nordic Body Map assessment of musculoskeletal disorders begins with the identification of workers' complaints using the SNQ, which can identify the part of the muscle that has caused the complaints.Keywords: Rapid Office Strain Assessment (ROSA), Muscoceletal Disorder, NBM